Heat transfer studies in microchannels - Mahulikar Shripad Prabhakar. (2008)
From a survey on studies on convection in microchannels, the Brinkman number is proposed as a parameter for correlating the Nusselt number. This proposal emerges from a dimensional analysis of the variables influencing the laminar forced convective heat transfer in microchannels, and explains the hitherto unusual behaviour of convective heat transfer in microchannels. The physical significance of the Brinkman number, as applicable to microchannels and its role in convective heat transfer are elaborated. The experimental data reported in the literature and those obtained from present experiments for the laminar regime heat transfer, correlate much better with the inclusion of the Brinkman number in the correlation. A dimensionless geometric parameter is also proposed in the correlation. The experimental data in the literature have also indicated that there are unexplained unusual behaviours associated with flow transitions in microchannels. In particular, the geometry of the microchannels and Reynolds number alone do not determine the flow regime boundaries and the transition range. The experimental data are processed based on the correlation of the single-phase convective heat transfer with the Brinkman number, from which the Reynolds and Brinkman numbers at the flow transition points are obtained for fixed microchannel geometry. The transition range is found to vary due to the difference in the extent of the rol6-played by the Brinkman number in determining the laminar-to-transition and transition-to-turbulent boundaries.